Design of an Arduino-Based Automatic Door Lock Using a Smartphone - Indra Philip Hutabarat (Journal Majelis Paspama, 2024)
The advancement of technology has encouraged various innovations to simplify human activities, including home security systems. One such innovation is the design of an automatic door lock system based on Arduino that can be controlled using a smartphone. This study aims to design and implement a more practical and secure automatic door lock system without the use of physical keys or keypads. The system utilizes the Bluetooth HC-05 module as a communication medium between the smartphone and the Arduino Uno microcontroller, which controls the relay and solenoid lock as the door actuator. The research methods applied include field research to collect empirical data and library research to establish theoretical foundations. The implementation results show that the automatic door lock system functions properly, allowing users to lock and unlock doors wirelessly through a smartphone application. This system is considered more efficient, practical, and capable of reducing the risk of losing keys or forgetting PINs found in conventional systems.